2016
DOI: 10.1111/jphd.12170
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence delivery of tobacco cessation support in general dental practice: a narrative review

Abstract: Organizational changes in dental practices to encourage more team working and professional time for lifestyle support may influence delivery. Dental professionals who are smokers may require training to develop their beliefs about the effectiveness of smoking cessation interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…Examples included having access to professional guidelines (Van Gerwen et al 2009), or an individual case management approach (Vine et al 2013) for the prevention and management of childhood obesity, and having structured protocols for smoking cessation advice (Rosseel et al 2012). Additionally, Lala et al concluded that support from colleagues was perceived to be important, where professionals working individually, compared with those having the support of a team, were more likely to perceive barriers to delivering behavior change interventions (Lala et al 2017).…”
Section: Beliefs About Resources and Support Needed To Facilitate Intmentioning
confidence: 99%
See 3 more Smart Citations
“…Examples included having access to professional guidelines (Van Gerwen et al 2009), or an individual case management approach (Vine et al 2013) for the prevention and management of childhood obesity, and having structured protocols for smoking cessation advice (Rosseel et al 2012). Additionally, Lala et al concluded that support from colleagues was perceived to be important, where professionals working individually, compared with those having the support of a team, were more likely to perceive barriers to delivering behavior change interventions (Lala et al 2017).…”
Section: Beliefs About Resources and Support Needed To Facilitate Intmentioning
confidence: 99%
“…Nine reviews highlighted context-specific factors that enabled delivery of behavior change interventions to patients: having the time to deliver interventions (Lala et al 2017), working in an environment perceived to be conducive to delivering interventions (Johnson et al 2011), and having an organizational system to support delivery of behavior change interventions (Gentry et al 2017). Yousefzadeh et al concluded that specialist anesthesiologists have the opportunity to deliver a brief intervention for smoking cessation, despite this only being part of a brief preoperative clinical encounter (Yousefzadeh et al 2016).…”
Section: Contextual Enablersmentioning
confidence: 99%
See 2 more Smart Citations
“…Although health care professionals are an expected and trusted source of behaviour change advice (McPhail & Schippers, 2012;Whitlock, Orleans, Pender, & Allan, 2002), the expectation that they will deliver health behaviour change interventions opportunistically is relatively new, and so may not be a core part of health care professional training or established practice. Systematic reviews cite knowledge and skills as barriers to addressing behaviour change with patients among GPs (Stead et al, 2009), dentists (Lala, Csikar, Douglas, & Muarry, 2017), and anaesthesiologists (Yousefzadeh, Chung, Wong, Warner, & Wong, 2016). However, although knowledge and skills are necessary for health care professionals to deliver opportunistic behaviour change interventions, they are not sufficient and health care professionals additionally require motivation and opportunity (Michie, Atkins, & West, 2014).…”
Section: Statement Of Contributionmentioning
confidence: 99%